Larvae of Drosophila melanogaster exhibit transcriptional activation of immune response pathways and antimicrobial peptides during recovery from supercooling stress. (February 2019) - Štětina, Tomáš; Poupardin, Rodolphe; Moos, Martin; Šimek, Petr; Šmilauer, Petr; Koštál, Vladimír
Abstract: The biochemical and molecular mechanisms underlying insect cold acclimation prior to cold stress are relatively well explored, but the mechanisms linked to recovery and repair after cold stress have received much less attention. Here we focus on recovery from cold stress in the larvae of the vinegar fly ( Drosophila melanogaster ) that were exposed to two physiologically distinct cold stress situations: supercooling (S, survival > 95%) and freezing (F, survival < 10%), both at −5 °C. We analysed the metabolic and transcriptomic responses to cold stress via GC-MS/LC-MS and whole-genome microarrays, respectively. Both stresses (S and F) caused metabolic perturbations which were transient in supercooled larvae but deeper and irreversible in frozen larvae. Differential gene expression analysis revealed a clear disparity in responses to supercooling and freezing (less than 10% of DE genes overlapped between S and F larvae). Using GO term enrichment analysis and KEGG pathway mapping, we identified the stimulation of immune response pathways as a strong candidate mechanism for coping with supercooling. Supercooling caused complex transcriptional activation of innate immunity potential: from Lysozyme-mediated degradation of bacterial cell walls, recognition of pathogen signals, through phagocytosis and lysosomal degradation, Toll and Imd signaling, to upregulation of genes coding for different antimicrobial peptides. The transcriptomic response to freezing was instead dominated by degradation of macromolecules and death-related processes such as autophagy and apoptosis. Of the 45 upregulated DE genes overlapping in responses to supercooling and freezing, 26 were broadly ascribable to defense and repair functions. Graphical abstract: Image 1 Highlights: Supercooling and freezing disturb metabolic networks transiently and irreversibly, respectively. Transcriptomic response to supercooling is dominated by upregulation of immune response pathways. Transcriptomic response to freezing contains few elements of immune response but is dominated by death-related processes.